The effect of topography and wettability of biomaterials on platelet adhesion. Issue 8 (17th April 2016) - Liu, Yabing; Zhang, Xiwen; Hao, Pengfei
Abstract: In this study, the effect of surface topography and wettability on the adsorption of albumin, fibrinogen, and platelet was investigated. In this experiment, silicon substrate with hydrophobic treatment, which has a micron-scale pillar structure was used. The proteins used were bovine serum albumin (BSA) and bovine fibrinogen (BFg), and platelet used was from human blood. BSA was fluorescently labeled with fluorescein isothiocyanate and BFg was fluorescently labeled with rhodamine B isothiocyanate. The experiment was conducted under shear flow condition, just like human blood vessels flow. In this study, BSA was preferentially adsorbed on hydrophobic surface, however BFg was adsorbed more on the hydrophilic surface. Fewer platelets were adhered on the hydrophobic surface. The lowest fibrinogen adsorption amount and the lowest platelet activity was observed on surfaces with specific interspacing of 6–8 μm, and BSA adsorption peaks at the height of 12 μm.The results shows that the hydrophobic surface has good anti-thrombogenicity and blood compatibility. Moreover, a surface with the characteristic scale similar to the platelet size is capable of inbibiting platelet adhesion and activation.